The Study of Waterbirds Diversity in Paya Indah Wetland, Selangor - Noor Amirah Ahmad Udin (2013)
The objectives of these studies were to identify the waterbird species diversity and to compare the frequency of occurrence of waterbird at five main sakes in Paya Indah Wetland, Selangor. Distance sampling point count method was used to survey the bird species. The study period was November 2012 to February 2013. A total of 267 individual waterbirds species representing five families and 18 species were recorded in five main lakes. The dominant species recorded are Amaurornis phoenicurus (54 observations, 20.22%), Porphyrio porphyrio (50 observations, 18.73%), while Actitis hypoleucos, lxobrychus cinnamomeus and kobtychus fiavicollis were rarest and only one observation. The result show Typha Lake was recorded seven species (55 individual); Teratai Lake 16 species (131 individual); 5 species (33 individual) were identified in Rusiga Lake and Utama Lake were recorded 6 species (19 individual) within four month. The highest waterbirds diversity was observed in Teratai Lake (Shannon's=2.24), while the lowest was in the Rusiga Lake (Shannon's=1.56). The highest waterbirds species richness was observed in Teratai Lake (Margalefs R=3.08), while the lowest was observed in Rusiga Lake (Margalers R=1.14). The evenness of individuals among the species was higher in Rusiga Lake (E=0.95) and lower in Teratai Lake (E=0.95). This study indicates that the vegetation types. human disturbance and environment surround lakes in Paya Indah Wetland are highly important in determine the diversity of the waterbirds species in each lake.